Towards a methodology for literature reviews in social sciences - Saur-Amaral, Irina (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
The emergence of the Internet, the generalized access to online databases and top journal presence in these databases generated a shift in how literature reviews are to be performed. While fifteen-twenty years ago, researchers in social sciences would focus their efforts in finding journal articles to analyze and they would read and use some dozens of articles in their research, nowadays efforts fall upon selecting the right set of articles, reading and synthesizing in such ways that helicopter and detailed views are combined. There is a generational gap between senior and junior researchers, which so far has turned difficult the development of a methodological perspetive of literature reviews in social sciences that bring together both perspetives. Our paper develops a methodology for literature reviews in social sciences, combining the systematic literature review approach, proposed and applied by several authors in management field (Kofinas & Saur-Amaral, 2008; I. Saur-Amaral & Amaral, 2010; Irina Saur-Amaral & Borges Gouveia, 2007; Thorpe, Holt, Macpherson, & Pittaway, 2005; Tranfield, Denyer, & Smart, 2003; Tranfield & Mouchel, 2002), with the traditional literature review approach (Cook & Leviton, 1980; Hart, 2006; Webster & Watson, 2002). We present compare perspetives, analyzing them from a critical perspetive and we propose a combined approach to be tested and used for research in social sciences, indicating key validity concerns to be taken into account. Results are useful for senior and junior researchers in social sciences, which undertake literature reviews for their own or for group research.